2022
DOI: 10.1002/pld3.461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trichoderma harzianum biofertilizer on growth, yield, and quality of Bupleurum chinense

Abstract: The use of chemical fertilizers and pesticides led to a decline in the quality and yield of Bupleurum chinense. The aim of this study was to determine the effects of Trichoderma harzianum biofertilizer on the growth, yield, and quality of radix bupleuri and microbial responses. The results showed that T. harzianum biofertilizer promoted the growth of B. chinense and increased the yield and quality of radix bupleuri. In addition, it increased the contents of NH4+–N, NO3−–N, available K, and available P and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, after receiving treatments, there were increases in the head weights and head yield of T3 of 40% and 37%, respectively, in comparison to the control. T. harzianum biofertilizer was investigated by Liu et al 50 for its effects on the growth, yield, and quality of Radix bupleuri and microbial responses. The findings revealed that T. harzianum biofertilizer promoted the growth of Bupleurum chinense and increased the yield and quality of radix bupleuri.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after receiving treatments, there were increases in the head weights and head yield of T3 of 40% and 37%, respectively, in comparison to the control. T. harzianum biofertilizer was investigated by Liu et al 50 for its effects on the growth, yield, and quality of Radix bupleuri and microbial responses. The findings revealed that T. harzianum biofertilizer promoted the growth of Bupleurum chinense and increased the yield and quality of radix bupleuri.…”
Section: Discussionmentioning
confidence: 99%
“…Provide protection from pathogens via JA signalling Zea mays [66] Antimicrobial activity Bupleurum chinense [67] Increase colonization of non-host mycorrhizal plants Arabidopsis thaliana, Brassica napus [68] Trichoderma koningii…”
Section: Enhance Plant Immunity Via Increasing Antioxidant Enzymesmentioning
confidence: 99%
“… Wu et al (2022) found that Trichoderma applied after fumigation significantly improved cucumber yield and the soil chemical properties. Liu L. et al (2022) found that biofertilizer containing T. harzianum increased the yield and quality of Bupleurum chinense , increased the content of available nutrients in the rhizosphere soil, and enhanced the activities of sucrase and catalase. Trichoderma spp.…”
Section: Introductionmentioning
confidence: 97%